The Gulf : the Bush presidencies and the Middle East - Cairo, Michael F., 1970- (Studies in conflict, diplomacy, and peace., 2012)
Presidents George H.W. Bush and George W. Bush both led the United States through watershed events in foreign relations: the end of the Cold War and the terrorist attacks of September 11, 2001. Many high-level cabinet members and advisers played important foreign policy roles in both administrations, most notably Dick Cheney, Colin Powell, and Condoleeza Rice. Both presidents perceived Saddam Hussein as a significant threat and took action against Iraq. But was the George W. Bush administration really just "Act II" of George H.W. Bush's administration? In The Gulf, Michael F. Cairo reveals how, despite many similarities, father and son pursued very different international strategies. He explores how the personality, beliefs, and leadership style of each man influenced contemporary U.S. foreign policy. Contrasting the presidents' management of American wars in Iraq, approach to the Israeli-Palestinian peace process, and relationships with their Israeli counterparts, Cairo offers valuable insights into two leaders who left indelible marks on U.S. international relations. The result is a fresh analysis of the singular role the executive office plays in shaping foreign policy.